2012
DOI: 10.2174/157488612800492717
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Outcome After Unintentional Overdosing of Rivastigmine Patches

Abstract: The presented case is a description of a rivastigmine overdose due to a medication error involving patches. This case indicates the importance of clear and unambiguous instructions to avoid administration errors with patches and to be vigilant to adverse drug reactions for early detection and correction of drug administration errors. In particular, instructions clearly indicating that only one patch should be applied at a time are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…14 Adult case reports report significant morbidity and death from rivastigmine exposure. [15][16][17] Our findings of higher rates of reported symptoms and health care facility evaluations with rivastigmine exposures are consistent with the increased morbidity seen in these prior case reports, and merit attention to more exposures from this drug in the years ahead.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…14 Adult case reports report significant morbidity and death from rivastigmine exposure. [15][16][17] Our findings of higher rates of reported symptoms and health care facility evaluations with rivastigmine exposures are consistent with the increased morbidity seen in these prior case reports, and merit attention to more exposures from this drug in the years ahead.…”
Section: Discussionsupporting
confidence: 84%
“…There are several prior reports of toxicity from rivastigmine patches in adults but none in pediatric patients. 16,18 Theoretically, these patches could pose a risk similar to those described with transdermal fentanyl or clonidine. 19,20 However, only 3 cases were reported in our study, and none reported any symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic case reports indicate however specific problems related with this drug form, such as incorrect use of multiple patches [3,4], ingestion of used or unused patches [5] and skin reaction [6]. Since potent drugs linked to serious adverse reactions are administered through transdermal patches, medication errors may lead to serious adverse health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The American Food and Drug Administration (FDA) states that opioids poses the highest risk of harm and death, among approved transdermal patches, because of their risk to cause respiratory depression [7] and has, along with other organizations, issued warnings regarding unsafe use of these patches [8,9]. There are also previous reports of serious and fatal cases due to erroneous administration of multiple patches of rivastigmine, an anticholinergic drug used to treat dementia [4,10]. Prevalence and characteristics of medications errors related to transdermal opioid patches has not been systematically compiled and presented in the scientific literature and such information is needed to develop effective preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, problems in correct identification of drug packages are likely to be associated with decreased adherence , as are difficulties in handling drugs during the personalization process (e.g. tablet splitting ), whereas errors in drug dosage and drug application are related to non‐response or toxicity . Hence, the prevention of drug administration errors appears important, particularly in the ambulatory care setting, where the incidence rate might be higher and subsequent strategies to counteract adverse outcomes following administration errors might be less accessible.…”
Section: Discussionmentioning
confidence: 99%